2019
DOI: 10.1111/iwj.13190
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with lower‐extremity amputation in patients with diabetic foot ulcers in a Chinese tertiary care hospital

Abstract: Providing a better understanding of the risk factors for amputation in this particular region, Hunan province, in China might help patients with diabetic foot ulcers receive timely and appropriate medical care and help prevent amputation. Diabetic foot ulcer patients referred to the Third Xiangya Hospital during the period between December 2014 and September 2018 were enrolled. Participants who underwent amputations and received conservative treatments were compared using univariate and multivariate analyses t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 69 publications
2
15
0
Order By: Relevance
“…To improve the quality of life of diabetic patients, development of the effective treatments for diabetic complications has been necessary and urgent. Diabetic ulcers, the most common diabetic complication, a devastating medical problem which may lead to amputation (Alexiadou & Doupis, 2012; Bekele & Chelkeba, 2020; Guo et al, 2019). Traditional treatments include the control of blood glucose levels and healing management, but the therapeutic effect remains limited (Everett & Mathioudakis, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…To improve the quality of life of diabetic patients, development of the effective treatments for diabetic complications has been necessary and urgent. Diabetic ulcers, the most common diabetic complication, a devastating medical problem which may lead to amputation (Alexiadou & Doupis, 2012; Bekele & Chelkeba, 2020; Guo et al, 2019). Traditional treatments include the control of blood glucose levels and healing management, but the therapeutic effect remains limited (Everett & Mathioudakis, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Similar results have been reported in previous studies. [21][22][23] These results show that IMA may also play an important role in the pathogenesis of diabetic foot ulcers.…”
Section: Discussionmentioning
confidence: 95%
“…We have shown that the main major amputation risk factors in patients with DFU and CLTI treated by ACT were MTHFR A1928C mutation, smoking, elevated CRP, and decrease in TcPO 2 . Many of these factors have been associated with amputations in other studies, but have not been evaluated after ACT [ 26 – 28 ].…”
Section: Discussionmentioning
confidence: 99%